Optimized Extraction of Total Flavonoid Content of Pummelo Peel by Response Surface Methodology and Their Antioxidant Activity - Jiang, Li-Qin; Shen, Xiao-Fang; Xia, Dao-Zhong (Asian Journal of Chemistry, 2014)
The aim of this work was to optimize extraction total flavonoid from Guangxi Pummelo peels by response surface methodology and study the antioxidative activity of the extraction. The effects of ethanol concentration, ratio of solid to liquid, extraction time and temperature on the yield of total flavonoid were assessed. The yield of total flavonoid under analysis optimum condition was also fore casted by Design-Expert Software 7.0 software. Antioxidant activity of the extract was evaluated by study scavenging capacity of hydroxyl radical and superoxide anion radical, respectively. The optimized extraction conditions were as follows: extraction with a 38 fold volume of 80 % aqueous ethanol solution for 1.75 h at 56 ºC. Under these conditions, the theoretical yield of total flavonoid was 7.25 % and the extract possessed high antioxidative activity. This method is scientific, reasonable and feasible. It also laid the foundation for research and application of total flavonoid in Pummelo peel.